Developing a systematic surveilance and enforcement activities for the enfor cement branch of thr department of land survey in Samarahan divison, Sarawak - Brahim, Lumpu. (1998)
This is an exploratory and descriptive study on the development of an effective planning and reporting system of surveillance and enforcement activities for the Enforcement Section of Land and Survey Department (LSD) in the Samarahan Division. The study primarily addresses the thematic concern of the department on the weaknesses of the existing practices in the Enforcement Section at the Divisional levels and the need to bring change in the system in order to cope with rapid development in the state. It sets out to describe and analyze the weaknesses of the existing practices and proposes the ways of improving the effectiveness of surveillance and enforcement in LSD.